Motivasi Petani Dalam Menggunakan Benih Padi Varietas Lokal - Rollinda Mustikaning Cahyo; Mustapit Mustapit; Dian Anggraeni (JURNAL AGRIBISNIS TERPADU, 2019)
The existence of local varieties of rice in Indonesia is now declining, and is on the verge of extinction. The farmers' paradigm changed to seeing the economic value of rice and made the orientation of farmers shift to the market, slowly leaving local rice seeds. However, in the village of Cimandiri there are still farmers who survive and prefer to use local rice paddy seeds for farming activities. The purpose of the study was to describe motivation and explain the reasons (explanation) of farmers in choosing the local paddy rice seeds. This research is a qualitative research with the determination of the informant purposive sampling. Data analysis was used using Miles and Huberman's analysis.The results of the study show that the motivation of farmers to choose to use local varieties of paddy seeds is to fulfill the needs of existence or existence and relatedness. Satisfactory indicators of the need for existence are easy to obtain paddy seeds, farmers do not need to buy seeds, and consumption. Indicator of fulfilling the need for linkages, namely social activities. The results of the study also indicate that there is a need for existence and linkages that are fulfilled at the same time. The reason farmers use the local paddy rice seeds is based on farmers' economic moral actions and farmer's rationality at one time. Indicators of farmer's moral economic actions are culture and norms. Whereas farmer rationality acts because farmers dare to take cultivation risks and post-harvest risks. this study also shows the farmers' moral theory of economics and the theory of farmer rationality can be done at one time to make a decision.